Cyclic peptide-poly(HPMA) nanotubes as drug delivery vectors: In vitro assessment, pharmacokinetics and biodistribution. (September 2018) - Larnaudie, Sophie C.; Sanchis, Joaquin; Nguyen, Tri-Hung; Peltier, Raoul; Catrouillet, Sylvain; Brendel, Johannes C.; Porter, Christopher J.H.; Jolliffe, Katrina A.; Perrier, Sébastien
Abstract: Size and shape have progressively appeared as some of the key factors influencing the properties of nanosized drug delivery systems. In particular, elongated materials are thought to interact differently with cells and therefore may allow alterations of in vivo fate without changes in chemical composition. A challenge, however, remains the creation of stable self-assembled materials with anisotropic shape for delivery applications that still feature the ability to disassemble, avoiding organ accumulation and facilitating clearance from the system. In this context, we report on cyclic peptide-polymer conjugates that self-assemble into supramolecular nanotubes, as confirmed by SANS and SLS. Their behaviour ex and in vivo was studied: the nanostructures are non-toxic up to a concentration of 0.5 g L −1 and cell uptake studies revealed that the pathway of entry was energy-dependent. Pharmacokinetic studies following intravenous injection of the peptide-polymer conjugates and a control polymer to rats showed that the larger size of the nanotubes formed by the conjugates reduced renal clearance and elongated systemic circulation. Importantly, the ability to slowly disassemble into small units allowed effective clearance of the conjugates and reduced organ accumulation, making these materials interesting candidates in the search for effective drug carriers.